Religious Orders and the ‘World’ (Brill, 2025)
This book shows how male members of Catholic religious orders fashioned themselves in their interactions with the sin-ridden “world” that they claimed to have renounced. Inspired by recent innovations in the cultural and social history of early modern Catholicism, the contributions explore regular clerics’ practices of symbolic communication, their role as mediators between universal beliefs and practices and particular cultures of piety, their position in social networks, their relationships with Protestants, and their interactions with women religious. In so doing, the book sheds new light on the variety of material and symbolic exchanges between religious orders and secular society.